EFEKTIVITAS ANTIVIRUS CIDOFOVIR PADA PASIEN CACAR MONYET DENGAN GEJALA BERAT - Signa Radityatama, I Gusti Lanang Agung; Suprapti, Herni (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2024)
Background: Monkey pox is an infectious disease caused by viruses of the family Poxviridae, genus Orthopoxvirus, which can infect humans, vertebrates and arthropods. Symptoms of monkey pox include increased body temperature, headache, muscle aches, weakness, swollen lymph nodes in the neck, armpits and groin, and skin rashes. Giving antivirals is very effective in treating monkey pox infections caused by the monkey pox virus. Cidofovir is an antiviral that is given intravenously, for the treatment of monkey pox patients. The effectiveness of cidofovir in cases of monkeypox in humans is still uncertain. However, this drug has been shown to fight poxviruses in in vitro and animal studies. Based on this background, researchers are interested in conducting research on